1970
DOI: 10.1002/1097-0142(197001)25:1<135::aid-cncr2820250120>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Five-year cancer cure: Relation to total amount of peripheral lymphocytes and neutrophils

Abstract: An analysis is made of the correlation existing between curability, by conventional treatment, of 589 cases of different types of cancer with reasonable possibilities of cure, and the total number of leukocytes in peripheral blood. A positive significant correlation is found between cancer curability and the total number of peripheral lymphocytes; a negative correlation is found between the total number of peripheral neutrophils (segmented and nonsegmented) and cancer curability. No correlation is found betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
2
2

Year Published

1970
1970
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(79 citation statements)
references
References 7 publications
1
74
2
2
Order By: Relevance
“…In general, SIR reflects a local and systematic chronic inflammation, which could be caused by various types of malignancies. Riesco et al initially reported the relationships between SIR and blood lymphocyte, monocyte, and platelet counts 22 . The Glasgow prognostic score, reported by Forrest et al for non-small-cell lung cancer, is widely known as an indicator of SIR 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, SIR reflects a local and systematic chronic inflammation, which could be caused by various types of malignancies. Riesco et al initially reported the relationships between SIR and blood lymphocyte, monocyte, and platelet counts 22 . The Glasgow prognostic score, reported by Forrest et al for non-small-cell lung cancer, is widely known as an indicator of SIR 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have indicated that the state of the Systemic Inflammatory Response (SIR) provides significant information about the prognoses of a variety of cancers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Neutrophil-lymphocyte ratio (NLR), which reflects SIR, has been reported as a prognostic factor in gastrointestinal cancers, including intrahepatic cholangiocarcinoma 19 and colorectal cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphopenia is common in advanced malignant disease and is an adverse prognostic indicator. 34 It may be induced or exacerbated by conventional chemotherapy and radiotherapy. In an in vivo MLR experiment, however, it was found that at the peak of MLR following injection of allogeneic cells, more than 20% of the host lymph node cells were IL-2 receptor (IL-2R) positive and the majority of these were Lyt-2 1 T cells and B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Already in 1970, Riesco [366] observed a positive correlation between cancer curability and the total number of lymphocytes, while a negative correlation was found with the total number of peripheral neutrophils (segmented and nonsegmented) when 589 cases of different cancer types were investigated. From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%